2002
DOI: 10.1002/app.11060
|View full text |Cite
|
Sign up to set email alerts
|

A water‐developable negative photoresist based on the photocrosslinking of N‐phenylamide groups with reduced environmental impact

Abstract: A water-developable negative photoresist based on the photocrosslinking of N-phenylamide groups was prepared by the copolymerization of 4-styrenesulfonic acid sodium salts (SSS) with N-phenylmethacrylamide (copolymer A) or p-hydroxy-N-phenylmethacrylamide (copolymer B), and its properties such as solubility changes, photochemical reaction, and photoresist characteristics were studied. The copolymer containing a relatively higher amount of SSS units was soluble in water. Solubility changes of the copolymers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
(27 reference statements)
0
26
0
Order By: Relevance
“…The mechanism of negative working is shown in Scheme 1. Several groups have reported various water-developable materials and their applications, such as base-amplifying copolymers and positive-working photoresist, flexographic printing plates consisting of a photosensitive matrix and the diffusion of unreacted component and positive working heat-sensitive imaging composition [5][6][7][8][9][10][11][12]. In our previous work [13], we have also studied a water developable thermo-sensitive latex film.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mechanism of negative working is shown in Scheme 1. Several groups have reported various water-developable materials and their applications, such as base-amplifying copolymers and positive-working photoresist, flexographic printing plates consisting of a photosensitive matrix and the diffusion of unreacted component and positive working heat-sensitive imaging composition [5][6][7][8][9][10][11][12]. In our previous work [13], we have also studied a water developable thermo-sensitive latex film.…”
Section: Introductionmentioning
confidence: 97%
“…Plenty of research articles about water-soluble or thermo-sensitive resins have been reported [8,[14][15][16][17][18][19][20]. Ramesh and Vasudevan [15] have synthesized new water-soluble epoxy ester for formulating high-performance water-based paints.…”
Section: Introductionmentioning
confidence: 98%
“…It is a well known method from photolithographic literature, and often used in microsystem technology [11], in which pendant chromophoric groups are attached to the polymer as crosslinkers. However, there are relatively few reports of gels being prepared via photo-crosslinking of water-soluble polymers [9,12,13]. In these reports, water-soluble polymers are used as water-developable photo-resists [13], as absorbents for nonionic surfactants with temperature adjustable adsorption properties [12], and for the preparation of LCST polymer systems [8,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Photoresists are widely used for the manufacture of microelectronics, silk screen printings, printed circuit boards, optical disks, color filter resists, and so on. [5][6][7] Typically, a negative-type photoresist consists of polymer binder, photosensitive polyfunctional monomer, photoinitiator, solvents and additives. 8,9 Acrylic monomers used to synthesize the binder contain the desired functional groups, such as benzyl, hydroxyl, carboxyl groups, etc.…”
Section: Introductionmentioning
confidence: 99%